Tarde de invierno = Winter afternoon - Luján, Jorge 1943-; Sadat, Mandana 1971- (Groundwood Books, 2006)
A little girl draws on the frosted window while waiting for her mother to return home
Keywords: Winter / Juvenile fiction; Mother and child / Juvenile fiction; Children / Juvenile fiction; Hiver / Romans, nouvelles, etc. pour la jeunesse; Mère et enfant / Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants; Invierno / Novela juvenil; Madre e hijo / Novela juvenil; Niños / Novela juvenil; Spanish language materials / Bilingjual; Kind; Mutter; Warten; Bilderbuch